How Psychological Safety Affects Team Performance: Mediating Role of Efficacy and Learning Behavior - Kim, Sehoon; Lee, Heesu; Connerton, Timothy Paul (Frontiers in Psychology, 2020)
This paper examines the mechanisms that influence team-level performance, which is critical to organizational effectiveness. It investigates psychological safety, a shared belief that the team is safe for interpersonal risk-taking, and a causal model mediated by learning behavior and efficacy. This model hypothesizes that psychological safety and efficacy are related, which have been believed to be the same-dimension constructs. It also explains the process of how learning behavior affects the team’s efficacy. According to a study of 104 field teams in a multinational enterprise in Korea, psychological safety did not affect team effectiveness. However, when mediated by learning behavior and efficacy, a full mediation effect was found. The result supports a well-known metaphor that psychological safety is the engine of performance, not the fuel. It also explains how individuals contribute to group performance under a psychologically safe climate, enhancing team processes. Based on the findings, this paper suggests theoretical and methodological implications for future research to maximize the effectiveness of teams.